Physicochemical Properties and Heavy Metal Concentration in Soil of Industrial Area, Zirani, Savar, Dhaka (Journal of Environmental Science and Natural Resources, 2015)
Zirani of Savar is an important industrial area of the country which provides wide range of potentiality for economic development. The purpose of the study was to observe the nutrient status and heavy metals concentration of the soil in Zirani, Savar, Dhaka. Nine soil samples were collected and analyzed through different methods for analyzing pH, OC, N, K, P, S and the heavy metals including Zn, Cd, Cu, and Pb, were investigated using Atomic Absorption Spectroscopy (AAS) technique. The analyzed result revealed the soil surrounding the dumping site was slightly acidic which is not harmful for agricultural production. The highest value of OC was recorded 2.14% at point 3 and the lowest value was 1.92% which was found in point 2 that is greater than the reference value. Except total N concentration, the amount of available P, K, and S were greater than their recommended level. In addition the result showed that the concentration of Cu and Pb were much higher than their recommended level and the maximum value of Cu was 0.09 ppm and 0.762 ppm was the maximum concentration of Pb. and the concentration of Zn and Cd were within tolerable limit. Zn at point 3 showed higher concentration which was 3.05 ppm. The maximum value of Cd was 0.09 ppm that was found at station 1 under point 3.J. Environ. Sci. & Natural Resources, 8(1): 65-68 2015